SENSITIVITY OF ERYTHROMYCIN AGAINST CORYNEBACTERIUM DIPHTHERIAE - Mutahhar, Alif; Puspitasari, Dwiyanti (Institute of Topical Disease Universitas Airlangga, 2020)
Diphtheria is an acute infection disease caused by Corynebacterium diphtheriae. It remains a problem in Indonesia in a recent several years especially in East Java Province, which suffered from an outbreak of diphtheria in 2011. Erythromycin is the second line antibiotics therapy for diphteria if the patient is allergic to penicillin, also serving as a prophylactic and carrier therapy for contact diphtheria. Erythromycin has been used for diphtheria for a very long time, but there is little recent data on its sensitivity against C. diphtheriae. The purpose of this study is to identify whether Erythromycin still has a strong antibacterial activity against Corynebacterium diphtheriae by invitro test. This was a descriptive study which observed the sensitivity pattern of erythromycin against Corynebacterium diphtheriae using the Epsilometer test (etest) as a diffusion technique. Samples used in this study were 30 isolates of toxigenic Corynebacterium diphtheriae strain mitis and gravis at the Center for Health Laboratory (BBLK) Surabaya obtained during 2011 until 2014. We retrieved the data based on gender, age, and districts of patients for each of the samples then analyzed them descriptively. In this study, a sensitivity test of 30 toxigenic Corynebacterium diphtheriae isolates revealed that 27 (90%) were sensitive to Erythromycin (average Minimum Inhibitory Concentration/ MIC) <0.016 Î¼g/mL and all were strain mitis, while 3 (10%) had intermediate sensitivity with MIC 1 Î¼g/mL (all were strain gravis). No resistance result was found from the sensitivity test. According to the result, we conclude that Erythromycin still has a strong antibacterial activity against Corynebacterium diphtheriae.